A Heterozygous LMF1 Gene Mutation (c.1523C>T), Combined With an LPL Gene Mutation (c.590G>A), Aggravates the Clinical Symptoms in Hypertriglyceridemia - Guo, Danxia; Zheng, Yingchun; Gan, Zhongzhi; Guo, Yingying; Jiang, Sijie; Yang, Fang; Xiong, Fu; Zheng, Hua (Frontiers in Genetics, 2022)
Hypertriglyceridemia is an important contributor to atherosclerotic cardiovascular disease (ASCVD) and acute pancreatitis. Familial hypertriglyceridemia is often caused by mutations in genes involved in triglyceride metabolism. Here, we investigated the disease-causing gene mutations in a Chinese family with hypertriglyceridemia and assessed the functional significance in vitro. Whole-exome sequencing (WES) was performed revealing that the severe hypertriglyceridemic proband carried a missense mutation (c.590G>A) in exon 5 of the LPL gene, as well as a novel missense mutation (c.1523C>T) in exon 10 of the LMF1 gene. Conservation analysis by Polyphen-2 showed that the 508 locus in the LMF1 protein and 197 locus in the LPL protein were highly conserved between different species. I-TASSER analysis indicated that the LMF1 c.1523C>T mutation and the LPL c.590G>A mutation changed the tertiary structure of the protein. A decrease in mRNA and protein expression was observed in 293T cells transfected with plasmids carrying the LMF1 c.1523C>T mutation. Subcellular localization showed that both wild-type (WT) and mutant LMF1 protein were localized at the cell cytoplasm. In the cell medium and cell lysates, these LMF1 and LPL gene mutations both caused a decreased LPL mass. Moreover, the combination of LMF1 and LPL gene mutations significantly decreased LPL levels compared to their individual effects on the LPL concentration. This ultimately contributes to the manifestation of severe hypertriglyceridemia.